DICTATORIAL GOVERNMENT AND MAPUCHE PEOPLE FROM 1973 UNTIL 1978. RECONFIGURATION OF THE CHILEAN COLONIALISM - Caniuqueo Huircapán, Sergio (Revista de Historia Social y de las Mentalidades, 2024)
This article discusses Mapuche people’s  diversity, unity and continuity elements within  the military dictatorship’s context, between  1973-1978. It is argued that the Mapuche  people, constituted by social subjects, generates  a response system that allows reassuring itself  as a single entity against colonialism. In this  way, we are going to present the speech, actions,  forms or strategies, from both the military and  the Mapuche people for intervening in the  political scene during this period, in the IX  region. We address facts, which in our view, are  relevant to understand antagonisms and unities,  and the elements that made possible both  identity and continuity as a people.
Keywords: Military dictatorship; Mapuche; Colonialism